Beet yellows virus replicase and replicative compartments: parallels with other RNA viruses - Gushchin, Vladimir A.; Solovyev, Andrey G.; Erokhina, Tatyana N.; Morozov, Sergey Y.; Agranovsky, Alexey A. (Frontiers in Microbiology, 2013)
In eukaryotic virus systems, infection leads to induction of membranous compartments in which replication occurs. Virus-encoded subunits of the replication complex mediate its interaction with membranes. As replication platforms, RNA viruses use the cytoplasmic surfaces of different membrane compartments, e.g., endoplasmic reticulum (ER), Golgi, endo/lysosomes, mitochondria, chloroplasts and peroxisomes. Closterovirus infections are accompanied by formation of multivesicular complexes from cell membranes of ER or mitochondrial origin. So far the mechanisms for vesicles formation have been obscure. In the replication-associated 1a polyprotein of Beet yellows virus (BYV) and other closteroviruses, the region between the methyltransferase (MTR) and helicase (HEL) domains (1a central region, 1a CR) is marginally conserved. Computer-assisted analysis predicts several putative membrane-binding domains in the BYV 1a CR. Transient expression of a hydrophobic segment (referred to here as CR-2) of the BYV 1a in Nicotiana benthamiana led to reorganization of the ER and formation of ~1-m mobile globules. We propose that the CR-2 may be involved in the formation of multivesicular complexes in BYV-infected cells. This provides analogy with membrane-associated proteins mediating the build-up of “virus factories” in cells infected with diverse positive-strand RNA viruses (alpha-like viruses, picorna-like viruses, flaviviruses, and nidoviruses) and negative-strand RNA viruses (bunyaviruses).